2017
DOI: 10.1371/journal.pone.0172481
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human aqueous humour proteome: A comparison of the genders

Abstract: Aqueous humour (AH) is an important biologic fluid that maintains normal intraocular pressure and contains proteins that regulate the homeostasis of ocular tissues. Any alterations in the protein compositions are correlated to the pathogenesis of various ocular disorders. In recent years, gender-based medicine has emerged as an important research focus considering the prevalence of certain diseases, which are higher in a particular sex. Nevertheless, the inter-gender variations in the AH proteome are unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…10 With variable relaxation or contraction of the ciliary muscle, the zonule of Zinn alters the convexity of the lens and subsequently changes the focal point of the eye. 11,12…”
Section: Orbital Anatomymentioning
confidence: 99%
“…10 With variable relaxation or contraction of the ciliary muscle, the zonule of Zinn alters the convexity of the lens and subsequently changes the focal point of the eye. 11,12…”
Section: Orbital Anatomymentioning
confidence: 99%
“…Going forward, it is expected that these results from an animal model will inform future translational studies. Although human proteomic AH analyses have been performed, 25,[28][29][30][31][32][33][34][35][36][37][38][39][40][41] few have applied this work to pediatric subjects. Therefore, data from the current study will support efforts that compare the AH proteins identified in juvenile rabbits to those found in infants in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the clear tendency in females, no significant differences between adult and aged mice were identified in males. This result may be due to the gender-based difference of composition ratio in the aqueous humor proteome [46].…”
Section: Discussionmentioning
confidence: 99%